Pathi's sister is still troubling - Naidoo, Savani (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of micro fiction, flash fiction, fairy tales, vignettes and short stories which explore the tension of being both an insider and an outsider. I have access to different cultures without belonging to any of them: as a child, my family moved from a South African Indian community to a formerly whites-only suburb; as an adult I have lived in South Korea, the United Arab Emirates and Sudan. My prose draws on my life experiences, family legends, neighbourhood gossip, news reports and historical events to question norms and ideas that I may have taken for granted had I been fully inside a single culture. In my thesis I frequently spell words phonetically to mimic how I hear or remember them. I also borrow words from languages I don't speak. I want the languages I use and mix to corrupt each other, as Raymond Federman put it, in order to better express the voices and contexts of the communities I draw inspiration from. Kuzhali Manickavel's Things We Found During the Autopsy showed me that culturally rich imagery can be used without interrupting narrative flow with explanations. I am also influenced by the poetic sense of rhythm and melody of Lydia Davis's minimalist prose, and by Sandra Cisneros's The House on Mango Street, where each concise short story stands alone but together creates a broad understanding of people and place. Anthologies such as PP/FF, edited by Peter Conners, and My Mother She Killed Me, My Father He Ate Me, edited by Kate Bernheimer, have inspired me to be bold in finding the form that best allows each narrative to be told.
Keywords: Creative writing (Higher education) -- South Africa; South African fiction (English) 21st century; Short stories, South African (English) 21st century; Diaries -- Authorship; Books Reviews